Perbandingan Kualitas Jaringan Provider Menggunakan Metode QOS (Quality Of Service) - Budi Hartono, Hendro Kartiko; Darmi, Yulia (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
The need for a reliable and efficient internet network is increasing along with the increasing number of users and the complexity of applications used by the community. With the increasing need for an internet network, many providers have emerged and become business fields, some of which are MyRepublic, myXL, and Telkomsel. The frequent occurrence of network signals that suddenly go down or are disconnected due to weather and network barriers is an obstacle in itself. Problems with network quality are a benchmark for someone who is choosing a service provider. Therefore, the final results of this research aim to determine the quality of MyRepublic, myXL, and Telkomsel provider networks using the QoS measurement method. The measurement data from the MyRepublic Provider has the smallest index result, seen at 3.51 ms with the category "very good" and also the MyRepublic Provider index produces 1.6 Mbps for the measurement of throughput parameters with the description "Very Good". The myXL provider produces the smallest packet loss measurement with an index of 0.02% with the category "very good". In the jitter measurements, the providers MyRepublic and myXL found the smallest value with an index of 0.0 ms with the category "very good"..   Keywords— QoS, Provider, analysis jaringan